166Holmium–99 mTechnetium dual-isotope imaging: scatter compensation and automatic healthy-liver segmentation for 166Holmium radioembolization dosimetry - Martina Stella; Arthur J. A. T. Braat; Marnix G. E. H. Lam; Hugo W. A. M. de Jong; Rob van Rooij (EJNMMI Physics, 2022)
Abstract Background Partition modeling allows personalized activity calculation for holmium-166 (166Ho) radioembolization. However, it requires the definition of tumor and non-tumorous liver, by segmentation and registration of a separately acquired CT, which is time-consuming and prone to error. A protocol including 166Ho-scout, for treatment simulation, and technetium-99m (99mTc) stannous phytate for healthy-liver delineation was proposed. This study assessed the accuracy of automatic healthy-liver segmentation using 99mTc images derived from a phantom experiment. In addition, together with data from a patient study, the effect of different 99mTc activities on the 166Ho-scout images was investigated. To reproduce a typical scout procedure, the liver compartment, including two tumors, of an anthropomorphic phantom was filled with 250 MBq of 166Ho-chloride, with a tumor to non-tumorous liver activity concentration ratio of 10. Eight SPECT/CT scans were acquired, with varying levels of 99mTc added to the non-tumorous liver compartment (ranging from 25 to 126 MBq). For comparison, forty-two scans were performed in presence of only 99mTc from 8 to 240 MBq. 99mTc image quality was assessed by cold-sphere (tumor) contrast recovery coefficients. Automatic healthy-liver segmentation, obtained by thresholding 99mTc images, was evaluated by recovered volume and Sørensen–Dice index. The impact of 99mTc on 166Ho images and the role of the downscatter correction were evaluated on phantom scans and twenty-six patients’ scans by considering the reconstructed 166Ho count density in the healthy-liver. Results All 99mTc image reconstructions were found to be independent of the 166Ho activity present during the acquisition. In addition, cold-sphere contrast recovery coefficients were independent of 99mTc activity. The segmented healthy-liver volume was recovered fully, independent of 99mTc activity as well. The reconstructed 166Ho count density was not influenced by 99mTc activity, as long as an adequate downscatter correction was applied. Conclusion The 99mTc image reconstructions of the phantom scans all performed equally well for the purpose of automatic healthy-liver segmentation, for activities down to 8 MBq. Furthermore, 99mTc could be injected up to at least 126 MBq without compromising 166Ho image quality. Clinical trials The clinical study mentioned is registered with Clinicaltrials.gov (NCT02067988) on February 20, 2014.